Edema induced by a crotalus durissus terrificus venom serine protease (Cdtsp 2) involves the PAR pathway and PKC and PLC activation - Costa, Caroline R. C. [UNESP]; Belchor, Mariana Novo [UNESP]; Rodrigues, Caroline F. B.; Toyama, Daniela de Oliveira [UNESP]; de Oliveira, Marcos A. [UNESP]; Novaes, Danielle P. [UNESP]; Toyama, Marcos Hikari [UNESP] (MDPI, 2018)
Snake venom serine proteases (SVSPs) represent an essential group of enzymatic toxins involved in several pathophysiological effects on blood homeostasis. Some findings suggest the involvement of this class of enzymatic toxins in inflammation. In this paper, we purified and isolated a new gyroxin isoform from the Crotalus durissus terrificus (Cdt) venom, designated as Cdtsp 2, which showed significant proinflammatory effects in a murine model. In addition, we performed several studies to elucidate the main pathway underlying the edematogenic effect induced by Cdtsp 2. Enzymatic assays and structural analysis (primary structure analysis and three-dimensional modeling) were closely performed with pharmacological assays. The determination of edematogenic activity was performed using Cdtsp 2 isolated from snake venom, and was applied to mice treated with protein kinase C (PKC) inhibitor, phospholipase C (PLC) inhibitor, dexamethasone (Dexa), antagonists for protease-activated receptors (PARs), or saline (negative control). Additionally, we measured the levels of cyclooxygenase 2 (COX-2), malondialdehyde (MDA), and prostaglandin E2 (PGE2). Cdtsp 2 is characterized by an approximate molecular mass of 27 kDa, an isoelectric point (pI) of 4.5, and significant fibrinolytic activity, as well as the ability to hydrolyze Nα-benzoyl-L-arginine 4-nitroanilide (BAPNA). Its primary and three-dimensional structures revealed Cdtsp 2 as a typical snake venom serine protease that induces significant edema via the metabolism of arachidonic acid (AA), involving PARs, PKC, PLC, and COX-2 receptors, as well as inducing a significant increase in MDA levels. Our results showed that Cdtsp 2 is a serine protease with significant enzymatic activity, and it may be involved in the degradation of PAR1 and PAR2, which activate PLC and PKC to mobilize AA, while increasing oxidative stress. In this article, we provide a new perspective for the role of SVSPs beyond their effects on blood homeostasis.
Keywords: COX-2; Crotalus durissus terrificus (Cdt); Edema; Inflammation; MDA; Oxidative stress; Protease-activated receptor; Snake venom serine protease